From body to community : venereal disease and society in Baroque Spain - Berco, Cristian (Toronto Iberic., 2015)
"Known in early modern Europe by many names--the French Disease, the Bubas, and, eventually, syphilis--the Great Pox was a chronic disease that carried the stigma of sexuality and produced a slow and painful death. The main institution which treated it, the pox hospital, has come down to us as a stench-filled and overcrowded place that sought to treat the body and reform the soul. Using the sole surviving admissions book for Toledo, Spain's Hospital de Santiago, Cristian Berco reconstructs the lives of men and women afflicted with the pox by tracing their experiences before, during, and after their hospitalization. Through an innovative combination of medical, institutional, and notarial sources, he explores the physical and social lives of the patients. What were the social repercussions of living with a shameful disease? What did living with this chronic illness mean for careers and networks, love and families, and everyday relationships? From Body to Community is a textured analysis at once touched by the illness but not solely defined by it."--